Use of tangerine peel extracts for the synthesis of magnetic nanocatalysts applied to the degradation of paracetamol - Oliveira, Jessica do Rocio de Paula de (2021)
This study describes the synthesis of an innovative nanomaterial (patent application number BR 1020210000317) composed of cobalt ferrite functionalized in niobium pentoxide CoFe2O4@Nb5O2 synthesized by green synthesis using tangerine peel extract. The material values the combination of a magnetic material (which allows easy recovery after application) with niobium pentoxide (whose metal is abundant in Brazilian territory). The synthesis was carried out with some temperature variations of the niobium calcination before joining with iron and cobalt salts and tangerine extract, the resulting materials were applied as catalysts in the degradation of Paracetamol by photocatalysis. The new materials were characterized by the following techniques: surface and pore analysis (SBET, SEXT, Smic, Vmic and VTOTAL), photoacoustic spectroscopy (PAS), point of zero charge (pHPZC), scanning electron microscopy (SEM/EDS) and X-ray diffraction (XRD). The studied reaction parameters included pH, catalyst concentration and radiation variation (different powers for the mercury vapor lamp). The results indicated that the CoFe2O4@Nb5O2 nanocatalysts were efficient in the degradation of Paracetamol (up to 99% degradation), showing better results under conditions of pH 1.0, catalyst concentration 103 mg L-1, under irradiation of the 250 W mercury vapor lamp (greater than 28 mW /cm²) at 240 minutes of the reaction.